Effect of Stressors on the mRNA Expressions of Neurosecretory Protein GL and Neurosecretory Protein GM in Chicks - Kato, Masaki; Iwakoshi-Ukena, Eiko; Narimatsu, Yuki; Furumitsu, Megumi; Ukena, Kazuyoshi (Frontiers in Physiology, 2022)
We recently discovered novel cDNAs encoding the precursors of two small secretory proteins, neurosecretory protein GL (NPGL) and neurosecretory protein GM (NPGM), in the mediobasal hypothalamus of chickens. In addition, we found colocalization of NPGL, NPGM, and histidine decarboxylase (HDC; histamine-producing enzyme) in same neurons of the medial mammillary nucleus of the hypothalamus. In this study, we elucidated the effect of several stresses, including food deprivation, environmental heat, inflammation, and social isolation, on the mRNA expression of NPGL, NPGM, and HDC in chicks using real-time PCR. Food deprivation for 24 h increased NPGM mRNA expression in the MBH. On the other hand, an environmental temperature of 37 °C for 24 h did not affect their mRNA expression. Six hours after intraperitoneal injection of lipopolysaccharide, an inducer of inflammation, the mRNA expression of NPGM, but not that of NPGL and HDC increased. Social isolation for 3 h induced an increase in the mRNA expression of NPGL, NPGM, and HDC. These results indicate that NPGM, but not NPGL or HDC, may participate in several physiological responses to stress in chicks.